(untitled) (International Journal of Functional Research in Science and Engineering (IJFRSE), 2026)
This study evaluates the potential of locally sourced clay minerals from Enugu State, Nigeria, for synthesizing zeolites applicable in water purification. Kaolinite-rich clay samples were collected from deposits in Nsukka, Obollo-Afor, and Emene, characterized using X-ray diffraction (XRD), X-ray fluorescence (XRF), and scanning electron microscopy (SEM) to determine their mineralogical and chemical compositions. The clays, primarily composed of kaolinite (60–75%) with minor quartz and illite, exhibited high silica (SiO₂: 45–50%) and alumina (Al₂O₃: 30–35%) contents, suitable for zeolite synthesis. Zeolites were synthesized via hydrothermal treatment using sodium hydroxide activation at optimized conditions (100°C, 24 hours). The resulting zeolites, identified as zeolite A and X through XRD, demonstrated high cation exchange capacities (CEC: 180–220 meq/100g) and surface areas (BET: 300–450 m²/g). Batch adsorption tests assessed their efficacy in removing heavy metals (Pb²⁺, Cd²⁺) and organic pollutants (methylene blue) from contaminated water, achieving removal efficiencies of 85–95% under optimal conditions (pH 6, 25°C, 2 g/L dosage). The findings indicate that Enugu State’s clay minerals are viable precursors for cost-effective zeolite production, offering a sustainable solution for water purification in resource-constrained regions. Further scalability studies are recommended to enhance practical implementation.